Sanksi Penundaan atau Penghentian Jaminan Sosial Pada Masa Pandemi COVID-19 - Ana Fauzia; Fathul Hamdani (University of Jember, Indonesia, 2021)
Social security program reflects state's responsibilities to provide social and economic protection to citizens. However, social security in Indonesia has remained to become a central issue after Presidential Regulation Number 14 of 2021. This regulation outlines administrative sanctions on delaying or terminating social security for citizens that refuse vaccines. This study examined the issue from philosophical, juridical, and sociological perspectives on the administrative sanctions for delaying or terminating the social security related to the vaccine requirements. This study used a legal research method with statutory, conceptual, and case approaches. This study indicated that the regulation regarding the postponement or termination of social security provision contradicted Article 20(1) of Law Number 40 of 2004 on the National Social Security System. Also, it violated human rights about the right to social security based on the 1945 Constitution. Instead, to succeed in vaccination, it should adopt a socio-cultural approach by combining legal instruments with elements of local culture in the community for legitimating vaccination as its part of being accepted in the society. KEYWORDS: Social Security Program, Presidential Regulation, Administrative Sanctions, Vaccines, COVID-19.